Social criticism of Sabir Rashid's novel” The Sword of Moses” - Darsim Saeed Sharif; Azad Mohamad Saeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Throughout the history of humankind and since the formation of various communities, each of these groups has gained a set of specific values and principles. Violating each of these values and principles leads to social issues, in which individuals face criticism and other problems. The reasons are some of these values and principles have national, religious and educational / upbringing aspects that bring wellbeing and stability to the whole community, in general. However, there are some social issues that need to be solved or things need to be reorganized somehow to cope with the advancement of the communities. The individual lives should not be ruined because of the observation of the old cultural and traditional values. Novels as a main genre of literature is a convenient way to understand and recognize social issues of various communities around the world. In Kurdish literature, the Sabir Rashid novel reflects the whole Kurdish community. It depicts the social issues and the values and principles, objectively and non-fundamentally.